Screen Adaptations and the Politics of Childhood Transforming Children's Literature into Film - McCallum, Robyn (Palgrave Studies in Adaptation and Visual Culture, 2018)
This book features a cutting edge approach to the study of film adaptations of literature for children and young people, and the narratives about childhood those adaptations enact. Historically, film media has always had a partiality for the adaptation of 'classic' literary texts for children. As economic and cultural commodities, McCallum points out how such screen adaptations play a crucial role in the cultural reproduction and transformation of childhood and youth, and indeed are a rich resource for the examination of changing cultural values and ideologies, particularly around contested narratives of childhood. The chapters examine various representations of childhood: as shifting states of innocence and wildness, liminality, marginalisation and invisibility. The book focuses on a range of literary and film genres, from 'classic' texts, to experimental, carnivalesque, magical realist, and cross-cultural texts. .